Neighborhood Quality and Labor Market Outcomes: Evidence from Quasi-Random Neighborhood Assignment of Immigrants - Anna Piil Damm (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2012)
Using survey information about characteristics of personal contacts linked with administrative register information on employment status one year later, I show that unemployed survey respondents with many employed acquaintances have a higher job finding rate. Settlement in a socially deprived neighborhood may, therefore, hamper individual labor market outcomes because of lack of employed contacts. I investigate this hypothesis by exploiting a unique natural experiment that occurred between 1986 and 1998 when refugee immigrants to Denmark were assigned to municipalities quasirandomly, which successfully addresses the methodological problem of endogenous neighborhood selection. Taking account of location sorting, living in a socially deprived neighborhood does not affect labor market outcomes of refugee men. Furthermore, their labor market outcomes are not affected by the overall employment rate of men living in the neighborhood, but positively affected by the employment rate of non-Western immigrant men and co-national men living in the neighborhood. This is strong evidence that immigrants find jobs in part through their employed immigrant and co-ethnic contacts in the neighborhood of residence and that a high quality of contacts increases the individual's employment chances and annual earnings.
Keywords: J60; J31; R30; 330; Residential job search networks; referral; contacts; neighborhood quality; labor market outcomes